Reproductive success in wild and hatchery male coho salmon. Issue 8 (August 2015) - Neff, Bryan D.; Garner, Shawn R.; Fleming, Ian A.; Gross, Mart R.
Abstract : Salmon produced by hatcheries have lower fitness in the wild than naturally produced salmon, but the factors underlying this difference remain an active area of research. We used genetic parentage analysis of alevins produced by experimentally mixed groups of wild and hatchery coho salmon ( Oncorhynchus kisutch ) to quantify male paternity in spawning hierarchies. We identify factors influencing paternity and revise previously published behavioural estimates of reproductive success for wild and hatchery males. We observed a strong effect of hierarchy size and hierarchy position on paternity: in two-male hierarchies, the first male sired 63% (±29%; s.d.) of the alevins and the second male 37% (±29%); in three-male hierarchies, the first male sired 64% (±26%), the second male 24% (±20%) and the third male 12% (±10%). As previously documented, hatchery males hold inferior positions in spawning hierarchies, but we also discovered that hatchery males had only 55–84% the paternity of wild males when occupying the same position within a spawning hierarchy. This paternity difference may result from inferior performance of hatchery males during sperm competition, female mate choice for wild males, or differential offspring survival. Regardless of its cause, the combination of inferior hierarchical position and inferior success at a position resulted in hatchery males having only half (51%) the reproductive success of wild males.